Higher fetuin-A, lower adiponectin and free leptin levels mediate effects of excess body weight on insulin resistance and risk for myelodysplastic syndrome. - Dalamaga, Maria; Karmaniolas, Konstantinos; Chamberland, John; Nikolaidou, Athina; Lekka, Antigoni; Dionyssiou-Asteriou, Amalia; Mantzoros, Christos S (Metabolism, 2013)
OBJECTIVE: Excess body weight has been implicated in the pathogenesis of myelodysplastic syndrome (MDS). We thus explored the role of serum fetuin-A reflecting ectopic hepatic fat deposition when storage capacity of adipocytes has been exceeded, free leptin reflecting overall fat mass and adiponectin reflecting visceral fat mass, all potential mediators of the effects of obesity on insulin resistance and, consequently, to MDS risk. MATERIALS & METHODS: In a hospital-based case-control study, we studied 101 cases with incident, histologically confirmed primary MDS and 101 controls matched on gender, age and date of diagnosis, between 2004 and 2007. Serum fetuin-A, adiponectin, leptin, leptin receptor, free leptin and insulin were determined. RESULTS: Higher serum fetuin-A, lower adiponectin and lower free leptin were all individually and independently associated with higher risk of MDS before and after controlling for matching and risk factors, such as age, gender, date of diagnosis, body mass index (BMI), family history of lymphohematopoietic cancer, smoking history and serum insulin. Interestingly, we have shown that these associations were prominent among overweight/obese individuals and persisted after controlling for BMI and serum insulin indicating that their effects are above and beyond insulinemia only. CONCLUSION: Elevated serum fetuin-A but lower adiponectin and free leptin are associated with higher risk of MDS particularly among overweight/obese individuals. These findings suggest that the association between excessive weight gain and the risk of MDS could be mediated by fetuin-A, adiponectin and free leptin, which may have potential clinical and preventive implications.
Keywords: Adiponectin; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Anthropometry; Body Mass Index; Confidence Intervals; Female; Humans; Insulin Resistance; Leptin; Male; Middle Aged; Myelodysplastic Syndromes; Obesity; Odds Ratio; Overweight; Prognosis; Receptors, Leptin